Cultural Sustenance in Language Education: Student Responses to Indigenous Knowledge Integration in Indonesian EFL Classrooms - Markus Lesa; Nehru P. Pongsapan; Charlie Baka (Universitas Cokroaminoto Palopo, 2026)
The marginalization of Indigenous Knowledge Systems (IKS) in formal education perpetuates colonial paradigms in postcolonial classrooms, yet empirical research on integrating local epistemologies into English as a Foreign Language (EFL) instruction in Indonesia's culturally distinct regions remains severely limited. This study aims to investigate the lived experiences of eighth-grade students at SMPN 6 Sa'dan, Tana Toraja Regency, who engaged with Toraja Indigenous Knowledge Systems within EFL vocabulary instruction across an eight-week pedagogical intervention. Employing a qualitative critical phenomenological design grounded in culturally sustaining pedagogy, decolonial language education, and critical language awareness, data were generated through triangulated multimodal methods: two phenomenological interviews per participant (60–90 minutes each), 32 hours of participant observation, weekly reflexive journals, and student-produced visual artifacts. Analysis followed Braun and Clarke's (2021) reflexive thematic analysis within a critical realist framework using NVivo 14. Findings revealed five interrelated dimensions of student experience: (1) epistemological reorientation, wherein English was reconceptualized from a symbol of Western dominance to a vehicle for indigenous meaning-making through 'reverse translation' practices; (2) heritage-positive identity reconstitution, documented in 11 of 12 participants; (3) affective transformation evidenced reduction in anxiety-related lexical items in student journals; (4) emergent critical language-culture consciousness concerning linguistic imperialism and cultural untranslatability; and (5) an unanticipated intergenerational knowledge exchange, wherein students became cultural mediators initiating bilingual documentation of elder knowledge. The study contributes a transferable heritage-sustaining language pedagogy framework, challenging Western-centric pedagogies in postcolonial Indonesian classrooms and offering practical implications for curriculum design, teacher education, and language policy in Indigenous and minoritized language contexts globally.